Contribution to the knowledge of the genus Visiana Swinhoe (Lepidoptera: Geometridae: Larentiinae), with the description of two new species from Indonesia - Schmidt, Olga (Zootaxa, 2018)
The present study contributes to the knowledge of the Indo-Pacific genus Visiana Swinhoe based on historic specimens collected in Indonesia and deposited in the collections of the Natural History Museum (London, UK) and Naturalis Biodiversity Center (Leiden, the Netherlands). Two new species V. cyclopsensis, sp. nov. from the Cyclops Mountains (West Papua) and V. minahasensis, sp. nov. from Minahasa (Sulawesi) are described and illustrated. These belong to two different species groups. An updated checklist of the genus Visiana, comprising 18 species is included.